Managing conflict how to make conflict work for you (Santa Monica, Calif. : Salenger Educational Media, 1978)
Dr. Marion Wood, a specialist in interpersonal and organization communication, explores some basic ways of dealing with conflict, and demonstrates how conflict, if managed properly, can work to one's advantage
Backup in VHS
Keywords: Social conflict; Interpersonal communication